2021
DOI: 10.3390/s21237993
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization for Mounting Primary Mirror with Reduced Sensitivity to Temperature Change in an Aerial Optoelectronic Sensor

Abstract: In order to improve the image quality of the aerial optoelectronic sensor over a wide range of temperature changes, high thermal adaptability of the primary mirror as the critical components is considered. Integrated optomechanical analysis and optimization for mounting primary mirrors are carried out. The mirror surface shape error caused by uniform temperature decrease was treated as the objective function, and the fundamental frequency of the mirror assembly and the surface shape error caused by gravity par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Further reduction in overall mass budget of the satellite system is also ensured by a reduction of the associated 3-point support framework behind each of the constituent sub-apertures. 47 As mentioned earlier, these suggested mirror configurations have a significant loss in collecting area but with very little blurring and inconsequential loss of contrast. This uncompromised imaging quality is achieved primarily due to pronounced sidelobe suppression in the resultant PSFs.…”
Section: Physical Designmentioning
confidence: 65%
“…Further reduction in overall mass budget of the satellite system is also ensured by a reduction of the associated 3-point support framework behind each of the constituent sub-apertures. 47 As mentioned earlier, these suggested mirror configurations have a significant loss in collecting area but with very little blurring and inconsequential loss of contrast. This uncompromised imaging quality is achieved primarily due to pronounced sidelobe suppression in the resultant PSFs.…”
Section: Physical Designmentioning
confidence: 65%
“…They include the rigid-body motion of the optical surface and higher-order surface distortion. The mathematical description of the Zernike polynomials for a distorted surface is defined as follows: 28 ΔZ(ρ,ξ)=A00+n=2An0Rn0(ρ)+n=1m=1nRnm(ρ)[Anm cos(mξ)+Bnm sin(mξ)],where ΔZ(ρ,ξ) denotes the deformed surface; ρ is the normalized radius of the reflection surface; ξ is the azimuth angle; Anm and Bnm are the Zernike coefficients in the X and Y…”
Section: Thermal Stability Analysismentioning
confidence: 99%
“…Wang et al established the forward and inverse kinematics model of the series spherical mechanism of the airborne photoelectric platform and verified them through joint simulation, improving the load ratio of platform [9] . Zhang carried out topology optimization on supporting structure model of Cassegrain optical system, which improved the optical performance and environmental adaptability of the main mirror supporting structure [10] . Yang et al has identified modal parameters of the reaction flywheel, providing reference for design of micro vibration suppression in optical remote sensing satellites [11] .…”
Section: Introductionmentioning
confidence: 99%